UJI DAYA HAMBAT EKSTRAK DAUN TAPAK KUDA (Ipomoea pes caprae (L) R. Br. ) TERHADAP Staphylococcus aureus - Alminsyah Alminsyah; Indria Hafizah; Sulastrianah Sulastrianah (Halu Oleo University, 2014)
Ipomoea pes caprae (L) R. Br are commonly used by the Indonesian’s people to treat wounds, ulcers and as antioxidant. Based on previous research it was contains terpenoids, saponins, alkaloids, tannins and flavonoids. The aim of this study is to determine inhibition capacity of I. pes caprae (L) R. Br leaf extract toward Staphylococcus aureus isolated from patients infected wounds at a concentration of 100 % , 50 % , 25 % , 12.5 % , 6.25 % , 3.125 % and 1.56 %. This research was conducted with post-test design with a control only. Erythromycin is used as a control. One gram of extract dissolved in 10 ml of chloroform. Inhibition zone is measured by paper disc diffusion method on Mueller Hinton agar. Bivariat analysis showed that there is statistically significant differences of diameters of inhibition zone from each concentration (p=0,00) including control (p=0,00). Conclusion of this study are I. pes caprae (L) R. Br leaf chloroform extract have capacity to inhibit S. aureus growth and the inhibition respond increase with concentration. Keywords : Ipomoea pes caprae (L) R. Br, Inhibition test, Erythromycin, Staphylococcus aureus